Advanced anaerobic digestion of municipal sludge using a novel and energy-efficient radio frequency pretreatment system. (1st July 2017) - Hosseini Koupaie, E.; Johnson, T.; Eskicioglu, C.
Abstract: Microwave (MW) sludge pretreatment systems are usually limited to a frequency of 2.45 GHz and the heating frequency is constrained by commercially available hardware. Studies using MW heating at this frequency have reported negative net energy balance (output energy as methane minus input electrical energy). This necessitates further research into more efficient thermal pretreatment technologies. In this research, a novel and highly efficient radio frequency (RF) pretreatment system at a frequency of 13.56 MHz was designed, implemented, and tested for the first time. The system was custom-designed based on the dielectric characteristics of thickened waste activated sludge (TWAS) to achieve a very efficient and uniform heating system. The effects of three factors including pretreatment method (RF vs. MW), final temperature (60, 90 and 120 °C), and stationary (holding) time (0, 1 and 2 h) on sludge solubilization and performance of mesophilic batch anaerobic digestion were evaluated simultaneously. Energy measurements were also made to compare the efficiency of the custom-designed RF and conventional MW heating systems. The differences in sludge disintegration (solubilization) using the RF and MW pretreatment systems were negligible (P > 0.05). No statistically significant difference was also observed between the two pretreatment systems in terms of mesophilic biogas production rate and extent (P > 0.05). The energy efficiency of the RF pretreatment system was measured between 67.3 and 95.5% for the temperature range of 25–120 °C which was significantly higher than that of the MW system efficiency which varied from 37 to 43%. Overall, the average input energy of the RF system was less than half of the energy consumed during the operation of the MW system to achieve a same target temperature. Considering the results of this research, the RF heating at a frequency of 13.56 MHz is suggested as an effective and energy-efficient technique for thermal hydrolysis of TWAS. Graphical abstract: Highlights: A novel 13.56 MHz radio frequency sludge pretreatment system was proposed for advanced AD. The system was custom-designed based on waste activated sludge dielectric characteristics. The designed RF system at 13.56 MHz was twice as efficient as the MW oven at 2.45 GHz. Uniform and homogeneous heating characteristics were achieved via RF pretreatment. Sludge disintegration and AD performance were independent of the pretreatment methods.